The law and economics of bargaining: an examination of the bargaining model employed by South Africa's Truth and Reconciliation Commission - Duffy, Jerrob (Centre for Law and Society, 2023)
Transitional justice methodology has emerged as an alternative to traditional retributive justice schemes when political transitions necessitate an accounting for human rights violations during prior regimes. As regimes move from illiberal to liberal, post-transition justice methodology has developed from the restorative justice model to engender truth and reconciliation. These normative concepts have evolved into a policy of creating truth and reconciliation commissions that trade civil and criminal amnesty with applicants in exchange for information. This bargained-for exchange can be analysed as an imperfect information game, where the commission attempts to maximise information(truth) while the applicant seeks amnesty for the lowest possible price. The game is similar to other bargaining games in law and economics, specifically plea-bargaining and bid-rigging during government auctions. Applying lessons learned from these problems, and employing game-theoretic analysis, this dissertation analyses the Truth-Amnesty game and puts it squarely within the law and economics framework. The analysis demonstrates that to maximise information gathering given the truth-reconciliation trade-off lexicographic ordering leads to an optimal Commission strategy.